Comparison of Harmonic scalpel and conventional homeostasis in understanding complications followed by total thyroidectomy - Munawer Latif Memon; Ijaz Ali; Brig Muhammad Ali; Sarwat Saeed (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE: Thyroidectomy is a classic surgical procedure used worldwide for thyroid gland excision. A study was conducted to compare the outcomes (mean operative time, drainage volume, postoperative pain and hospital stay) and postoperative complications of Harmonic scalpel and conventional homeostasis in patients who underwent total thyroidectomy METHODOLOGY: A prospective observational study was conducted at the department of general surgery, POF hospital Wah Cantt. The study duration was six months (June 2020-Novemebr 2020). A sample size of 70 patients was calculated using the WHO calculator. Patients for total thyroidectomy were selected through a non-probability consecutive sampling. Patients whose total thyroidectomy was planned were divided into two groups using a random number table. In Group A, we used a harmonic scalpel, while in Group B, we used the conventional homeostasis method to secure homeostasis operatively. Patients were followed after 4 weeks for complications. Chi-Square test and t-test was applied. RESULTS: A total of 70 patients were included in the study. The mean operative time was 44.5 min±1.4 in the HS group and 66.0 min±2.0 in the conventional homeostasis group (p≤0.001). Hospital stay was significantly less in the HS group as compared to the conventional homeostasis group (2.3 days ±0.4 vs 3.3 days ±0.4, p≤0.001). Postoperative drainage was significantly high in conventional homeostasis group as compared to HS group (56.4±1.5 mL vs 36.5±1.5 mL, p≤0.001). CONCLUSION: Harmonic scalpel is an effective, reliable and safe tool for better outcomes in terms of less operative time, lower drainage volume and short duration of hospital stay as compared to conventional methods.